2015
DOI: 10.1002/jca.21412
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of therapeutic plasma exchange by using apheresis devices in pediatric atypical hemolytic uremic syndrome patients

Abstract: TPE is a safe and effective therapeutic modality in pediatric aHUS if instituted early in the course of disease with a minimum of four to five procedures. J. Clin. Apheresis 31:381-387, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
(22 reference statements)
1
8
1
2
Order By: Relevance
“…27 However, financial constraints and non-availability of eculizumab limit its use in many clinical settings. The current findings, along with those of a previously published study that investigated 30 paediatric patients with complement-mediated TMA that were treated with PE, 28 suggest that haemopurification might be a viable and more costeffective alternative to eculizumab.…”
supporting
confidence: 70%
“…27 However, financial constraints and non-availability of eculizumab limit its use in many clinical settings. The current findings, along with those of a previously published study that investigated 30 paediatric patients with complement-mediated TMA that were treated with PE, 28 suggest that haemopurification might be a viable and more costeffective alternative to eculizumab.…”
supporting
confidence: 70%
“…Haque et al has also observed trivial adverse effects in 18/130 (13.8%) procedures in pediatric patients in intensive care units [36]. However, Study by Hans et al has shown much lower (7.69%) incidence of adverse events in 30 pediatric patients of atypical Hemolytic Uremic Syndrome (aHUS) and recommended early initiation of TPE in atypical HUS as reported earlier by Sharma et al from same centre [37,38]. Three types of complications appear to be more common and serious in children than in adults and are sometimes difficult to recognize at an early stage.…”
mentioning
confidence: 69%
“…However, the cost of the treatment is prohibitive for veterinary patients ( 25 , 27 ). For both these conditions, PEX is considered a standard treatment and has been shown to reduce mortality ( 1 , 8 , 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the major goals of PEX in TTP are the removal of the antibodies against ADAMTS-13 and the supplementation of ADAMTS-13 via FFP, preventing further thrombi formation. Similarly, in aHUS PEX can remove the aberrant complement and provide replacement with normal complement factors ( 28 ). In people with TMA, PEX with FFP has shown a reduction in mortality compared to single plasma infusion alone ( 7 , 29 ).…”
Section: Discussionmentioning
confidence: 99%